Social Media, Gen Z and Consumer Misbehavior: Instagram Made Me Do It - Jacobsen, Stephanie L.; Barnes, Nora Ganim (Journal of Marketing Development and Competitiveness, 2020)
It has long been held that consumer misbehavior could be attributed to a number of motivations, the strongest of which was the pressure of living in a consumption-oriented society and the heavy influence of marketing. The findings in this study suggest that with the influence of social media, Generation Z consumers are feeling internal pressure, in turn impacting their moral compass and leading to misbehavior in the marketplace. While commercial pressures are also recognized, this is the first empirical evidence that there might be a different, primary motivation.